ANALISIS YURIDIS PELAKSANAAN ALIH FUNGSI ASET PEMERINTAH MELALUI PROGRAM BUILD OPARATE AND TRANSFER (BOT) ANTARA PEMERINTAH KOTA TEBING TINGGI DENGAN PT. INTI GRIYAPRIMA SAKTI - EARLY WULANDARI SILONDAE (PREMISE LAW JURNAL, 2014)
ABSTRACT Build Operate Transfer (BOT) Agreement is a kind of unanimous agreement (onbenoemdeovereenkomst). The research used descriptive analytic approach with the source of primary and secondary data. In answering the formulation of the problems, the researcher used theoretical framework as the means of analysis; that is, the theory of legal certainty. The data were gathered by conducting library research and interviews and analyzed by using qualitative analysis method. The main legal basis for the implementation of Build Operate Transfer (BOT) of Ramayana Department Store, TebingTinggi is Government Regulation No. 6/2006 on the Management of State’s/Region’s Owned Property and the Decree of Minister of Internal Affairs No. 17/2007 on March 21, 2007 on the Technical Guidance for the Management of Regional Government Property. Mutual agreement between TebingTinggi City Administration and PT. IntiGriya Prima Sakti No. 644.I/2296/Bapp/2008 and No. 037/IGPS-SMG/TTG/III/08 were signed on March 5, 2008 with the object of the land ex-Bus Terminal, TebingTinggi which was known as Pondok Sri Padang (PSP) JalanJendralSudirman in the area of ± 8,535 square meters for the period of 25 years. Keywords: Build Operate Transfer Agreement, Management of Property Owned by TebingTinggi City Administration, PT. IntiGriya Prima Sakti